The Snakes and Ladders Game as Indonesian Cultural Literacy for Students - Atmi, Ragil Tri; Luthfiah, Dinda (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
Knowledge of Indonesian culture among students at SDN Mojo III Surabaya needs to be increased, so that this knowledge is easily accepted, the library uses an approach through traditional games. The game of snakes and ladders inserts images of Indonesian cultural characteristics, this is intended for students to know, understand, and appreciate Indonesian culture. The methods used include the preparation stage, making the game technically, implementing activities, results, and evaluating. The results obtained after implementing the game are proven to be able to increase Indonesian cultural literacy in students, this is evidenced by the ability of each student to easily understand and remember, then be able to convey it smoothly through verbal communication. The benefits are that students become more familiar with and understand the diverse Indonesian culture and provide motor skills and memory about Indonesian culture. The conclusion from this activity is that the game of snakes and ladders can increase the cultural literacy of students at SDN Mojo III Surabaya.